Strategi Pengembangan Banjir Kanal Barat Sebagai Daya Tarik Wisata Di Kota Semarang - Kismartini Kismartini; Hendra Kurniawan; Septi Anjani Putri Dwika (Faculty of Social and Political Sciences, Universitas Diponegoro, 2018)
The number of tourists visiting Semarang City is increasing significantly year by year. However, this increase is not accompanied by an improvement in the quantity and the quality of tourist destinations in Semarang. Banjir Kanal Barat area is one of the potential tourist destinations in Semarang, but so far the existing facilities in this area are very limited. In addition, there is no any tourism activities which can be done even. Moreover, this area tends to be very unattractive. This study aims to analyze the development strategy of Banjir Kanal Barat (BKB/western canal) as an interesting tourism destination by analyzing internal and external factors. The data were analyzed descriptively qualitative to determine BKB's development strategy through SWOT analysis (Strengths, Weaknesses, Opportunities, and Threats). The results of this study formulated 10 (ten) alternative strategies for the development of Banjir Kanal Barat as a tourism destination area. The three best alternative choices are: (1) creating tourist facilities which can be enjoyed by the community, (2) developing special water attractions, (3) inviting investors and cooperating with various parties.